High-Temperature Treatment to Improve the Capacity of LiBC Anode Material in Li-ion Battery - Yang, Qianwen; Chen, Langlang; Feng, Xiang; Li, De; Chen, Yong (Frontiers in Energy Research, 2020)
As a graphite-like material, the LiBC can deliver a high capacity as an anode material in Li-ion batteries, which was strongly dependent on the carbon precursor. Developing a method to improve the capacity would be significant to study and utilize the LiBC anode material. Here we treated a pristine LiBC material with a high temperature to obtain four modified LiBC samples, and a reversible capacity of 353 mAh/g was delivered by a modified LiBC sample that was treated at 600 °C for 10h in a powder form wrapped with an Al foil, which was only 218 mAh/g for the pristine LiBC in Li-ion batteries. According to the XRD result, the layer structure of LiBC was maintained after the high-temperature treatment, while the lattice parameters were changed slightly, especially for the interlayer distance. And the modified LiBC samples showed the similar Raman spectra as the pristine LiBC except for the peak intensity, which indicates the lithium evaporation during the high-temperature treatment. Thereby, the high-temperature treatment can improve the capacity of LiBC through reducing the lithium content and modifying the crystal structure, and this method would make the LiBC material become a more promising anode materials in Li-ion batteries.